Impact of Interpersonal Communication on Increasing Employees Job Satisfaction PT. PJS Palembang - Susi Handayani; Ricko Mahendra (Enrichment : Journal of Management, 2022)
Susi Handayani conducted research with the aim of knowing the impact of interpersonal communication and compensation on job satisfaction of employees of PT. PJS Palembang. This study uses a quantitative method approach with a sample of 90 respondents who are employees of PT. PJS Palembang. After being tested partially and simultaneously, it was stated that interpersonal communication and compensation had an impact on increasing job satisfaction, as indicated by the fcount 82.321 > ftable and 0.000 < 0.05. The results of the study stated that interpersonal communication and compensation had an impact on increasing job satisfaction of PT. PJS Palembang is 65.4%.